PENGARUH PENGGUNAAN MODEL PEMBELAJARAN TALKING STICK TERHADAP PENGUASAAN MATERI SISWA - Yulia Susidawati; Pramudiyanti Pramudiyanti; Berti Yolida (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2014)
This experiment aimed to find out the use of applicating cooperative learning model type talking stick towards improvement of students learning activities and outcomes. The research designs were non equivalent pretest – posttest. The research sample were students in VII1 and VII2 class that was selected by cluster random sampling. Data of the research were qualitative and quantitative. The qualitative data was gotten by students learning activity and questionnaire that was analyzed descriptively. The quantitative data was the average score of test, that was analyzed by t-test and U-test. The result of this study shown that the average of students outcomes in experimental class are higher than control (experiment= 77.92; control = 61.08). The average of student learning activities percentage in all observed aspects in experimental class shown higher enhancement than control (experiment = 82.22; control = 66.66). In addition,  the students also gives positive responses to applicating cooperative learning model type talking stick.Penelitian ini bertujuan untuk mengetahui penggunaan model pembelajaran talking stick terhadap aktivitas dan penguasaan materi siswa. Desain penelitian adalah pretes-postes tak ekuivalen. Sampel penelitian adalah siswa kelas VII1 dan VII2 yang dipilih secara cluster random sampling. Data penelitian berupa data kualitatif dan kuantitatif. Data kualitatif diperoleh dari aktivitas belajar siswa dan angket tanggapan siswa yang dianalisis secara deskriptif. Data kuantitatif diperoleh dari rata-rata nilai tes yang dianalisis menggunakan uji-t dan uji-U. Hasil penelitian menunjukkan hasil belajar  kelas eksperimen lebih tinggi (eksperimen = 77,92; kontrol = 61,08). Rata-rata persentase aktivitas siswa semua aspek kelas eksperimen juga menunjukkan peningkatan yang lebih tinggi (eksperimen = 82,22; kontrol = 66,66). Selain itu, semua siswa memberikan tanggapan positif terhadap penggunaan model pembelajaran talking stick.Kata kunci : aktivitas belajar, penguasaan materi, talking stick